2007
DOI: 10.1074/jbc.m611242200
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Fingers Subdomain of Escherichia coli DNA Polymerase I in the Strand Displacement Synthesis of DNA

Abstract: The replication of the genome requires the removal of RNA primers from the Okazaki fragments and their replacement by DNA. In prokaryotes, this process is completed by DNA polymerase I by means of strand displacement DNA synthesis and 5-nuclease activity. Here, we demonstrate that the strand displacement DNA synthesis is facilitated by the collective participation of Ser 769 , Phe 771 , and Arg 841 present in the fingers subdomain of DNA polymerase I. The steady and presteady state kinetic analysis of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 28 publications
9
59
1
Order By: Relevance
“…Although strand displacement synthesis and single stranded primer extension synthesis are expected to have substantial differences in their energetics, we compared our results to experiments that measured single stranded primer extension synthesis and found surprising agreement. Our observed rate of 14 nt sec Ϫ1 is consistent with bulk primer extension experiments (17,20). The rates measured here are 2-to 3-fold faster than a Pol I(KF) single molecule measurement (13), which was a low tension force spectroscopy study on a long template that did not have sufficient time resolution to separate pauses from bursts.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Although strand displacement synthesis and single stranded primer extension synthesis are expected to have substantial differences in their energetics, we compared our results to experiments that measured single stranded primer extension synthesis and found surprising agreement. Our observed rate of 14 nt sec Ϫ1 is consistent with bulk primer extension experiments (17,20). The rates measured here are 2-to 3-fold faster than a Pol I(KF) single molecule measurement (13), which was a low tension force spectroscopy study on a long template that did not have sufficient time resolution to separate pauses from bursts.…”
Section: Resultssupporting
confidence: 84%
“…This is likely why our 29 rate is slightly less than the reported 29 bulk rates of 38 nt sec Ϫ1 (29). A recent bulk study of Pol I(KF) reported a strand displacement synthesis rate over an 18-bp template of 1.2 nt sec Ϫ1 (20), which is an order of magnitude slower than our time-averaged burst synthesis rate. However, the template used in the bulk study contained three Pyr-G-C pause motifs.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations